Tradycjonalizm a dyktatura. Francisco Elías de Tejada y Spínola wobec frankizmu - Bartyzel, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The protagonist of the article is Francisco Elías de Tejada y Spínola 1917–1978 — philosopher of law and politics, theorist of natural law, professor of Universities of Salamanca, Seville and Madrid, one of the most distinguished exponents of 20th-century Spanish traditionalism, associated with the legitimist monarchist movement known as Carlism named after Don Carlos de Borbón. The author of the article focuses on the thinker’s attitude to the theory and practice of Francoist dictatorship, aperiod coinciding with the philosopher’s almost entire creative life. That attitude evolved considerably, aprocess in which three stages can be distinguished. In the first and shortest stage, between 1939 and 1941, Elías de Tejada was an enthusiast of the national-syndicalist state and theorist of the caudillaje system of power. In the second stage 1941–1955, starting from a distinction between dictatorship and caudillaje, now equated only with rightful and traditional monarchy, he became aradical and intransigent opponent of General Franco’s personal dictatorship, calling it scornfully “Caudiland” and seeing the authoritarian regime as one of the forms of political modernism and totalitarianism, contrary to the Spanish and Catholic tradition. In the third stage from 1955 to Franco’s death, while not changing his critical opinion of the regime and its leader, he tended to pursue a“possibilistic cultural policy” within the regime, promoting traditionalistic values and assuming that the dictatorship could evolve into atraditional monarchy.
Keywords: tradycjonalizm; frankoizm; dyktatura; monarchia; karlizm